(untitled) (International Journal of Food and Nutritional Sciences, 2021)
A comparative study is a process of conducting studies of two or more subject with respect of their features. It is a comparison of their respective pro and cons. This way of a study helps in finding out a best thing from the compared things. Here I made a comparative study on direct investing in equity shares and investing in mutual funds. The objective of the study is to identify the reasons for preferring equity and mutual fund and also know about the factor which affecting the behavior of the investors while they invest into mutual fund and equity market. This study is in descriptive nature since it is based on primary data ‘s facts and findings of investigation in a structured manner. People need a systematic way of investing should go for mutual fund investing. If an investor has got time in making a market study and managing his/her portfolio, should invest in equity shares directly, otherwise go for mutual fund investing